PENGARUH WORK LIFE BALANCE DAN LOCUS OF CONTROL TERHADAP KINERJA KARYAWAN PADA PT. BENGKULU SAMUDERA TEHNIK - Mujiyati, Mujiyati; Kusuma, Merta (UM. Bengkulu, 2025)
This study aims to analyze the influence of work life balance and locus of control on employee performance at PT. Bengkulu Samudera Tehnik, both individually ( partial) and simultaneously. Several key factors examined in reserch include work life balance and locus of control. The research subjects consist 70 employees from Bengkulu Samudera Tehnik. In data collection, this study employs observation, questionnarire distribution, and interviews. There are several data analysis techniques used in this study, including using instrument tests, classical assumption tests, respondent response analysis, multiple linear regression analysis, coefficient of determination, and hypothesis testing. From the results of multiple linear regression tests, the regression equation is obtained as follows: Y = 0.552 X1 +0.100 X2. The results of the t hypothesis test on the work life balance variable show t count > t table (40.62> 1.667) and sig (0.00 < 0.05), the locus of control variable shows t count < t table (0.759 < 1.667). The f test results show the value of f count 11.790> f table 3.13 and sig 0.00 < 0.05. So it can be concluded that work life balance and locus of control have a simultaneous and significant effect on employee performance at PT Bengkulu Samudera Tehnik. Keywords: work life balance, locus of control and employee performance